The false widow link between neutron star X-ray binaries and spider pulsars. Issue 3 (3rd February 2023) - Knight, Amy H; Ingram, Adam; van den Eijnden, Jakob; Buisson, Douglas J K; Rhodes, Lauren; Middleton, Matthew
ABSTRACT: The discovery of transitional millisecond pulsars (tMSPs) provided conclusive proof that neutron star (NS) low-mass X-ray binaries (LMXBs) comprise part of the evolutionary pathway towards binary millisecond pulsars (MSPs). Redback and black widow 'spider' pulsars are a subcategory of binary MSPs that 'devour' their companions through ablation – the process through which material is lifted from the stellar surface by a pulsar wind. In addition to reducing the companion star's mass, ablation introduces observable characteristics like extended, energy-dependent, and asymmetric eclipse profiles in systems observed at a sufficiently high inclination. Here, we present a detailed study and comparison of the X-ray eclipses of two NS LMXBs: Swift J1858.6 − 0814 and EXO 0748 − 676. Some of the X-ray eclipse characteristics observed in these two LMXBs are similar to the radio eclipse characteristics of eclipsing redback and black widow pulsars, suggesting that they may also host ablated companion stars. X-ray irradiation or a pulsar wind could drive the ablation. We conduct orbital phase-resolved spectroscopy for both LMXBs to map the column density, ionization, and covering fraction of the material outflow. From this, we infer the presence of highly ionized and clumpy ablated material around the companion star in both systems. We term LMXBs undergoing ablation, false widows, and speculate that they may be the progenitors of redback pulsars under the assumption that ablation begins in the LMXB stage. Therefore, the false widows could provide a link between LMXBs and spider pulsars. The detection of radio pulsations during non-accreting states can support this hypothesis.